The effect of audit opinion, financial distress, and good corporate governance on audit delay - Sugiyanto Sugiyanto (Universitas Pamulang, 2022)
This research examines the effect of financial distress, audit opinion, and good corporate governance on audit delays in Indonesian mining sector companies. By using panel data regression analysis, this study found that financial distress positively affects audit delay. Meanwhile, audit opinions and GCG are not proven to affect audit delay.AbstrakPenelitian menguji pengaruh financial distress, opinion audit, dan good corporate governance terhadap audit delay pada perusahaan-perusahaan sektor pertambangan Indonesia. Dengan menggunakan analisis regresi data panel, penelitian ini menemukan bahwa financial distress berpengaruh positif terhadap audit delay. Sementara itu, opini audit dan GCG tidak terbukti mempengaruhi audit delay.